Queen Bee Larva, an Edible By-Product of Royal Jelly, Alleviate D-Galactose-Induced Aging in Mouse by Regulating Gut Microbiota Structure and Amino Acid Metabolism - Tong Zhao; Xiaofeng Xue; Pingxiang Liu; Han Hu; Kai Wang; Yutao Wang; Liming Wu (MDPI AG, 2024)
Queen bee larva (QBL), as a by-product of royal jelly, is a kind of protein-rich edible insect. However, the development and utilization of QBL have been very limited for an extended period, resulting in considerable economic waste. Notably, QBL has substantial potential for anti-aging treatments; however, systematic studies have been scarce. The present study aimed to analyze the effects of freeze-dried QBL powder (QBLP) treatment in a D-galactose (D-gal)-induced-aging mouse and to explore the mechanisms. A behavioral test indicated that QBLP-treated mice had improved cognitive function and memory decline caused by aging compared to untreated aged mice. Furthermore, QBLP treatment improved organ index in aged mice and prevented pathological damage to the brain tissue. Concomitantly, treatment of D-gal-induced-aging mice with QBLP significantly reduced the oxidative damage of serum and increased the skin moisture content of aging mice. Finally, integrated analyses of the gut microbiota and the serum metabolome showed that QBLP supplementation altered the composition of the gut microbiota, enriched biochemical pathways associated with amino acid metabolism, and adjusted serum concentrations of beneficial free amino acids. Overall, QBLP can improve symptoms related to D-gal-induced aging in mice by regulating gut microbiota structure and amino acid metabolism.